UNRAVELING THE MYSTERY OF AUDIT DELAY: HOW FINANCIAL PERFORMANCE AND NON-FINANCIAL FACTORS AFFECT AUDIT TIMING - Harke Revo Leonard Polii; Jenny Morasa; Heince R.A Wokas (Universitas Sam Ratulangi, 2023)
This study aims to measure the effect of audit delay on the financial statements of the Indonesian manufacturing industry. Financial performance is measured by profitability, solvency, company size and non-financial performance is measured by the good corporate governance index. Financial and non-financial performance as independent variables while audit delay as the dependent variable. The population of this study are all manufacturing industries listed on the Indonesia Stock Exchange that submit annual financial reports for the 2018 and 2020 periods. The sample of this study is manufacturing companies listed on the Indonesia Stock Exchange in 2018 and 2020, the accounting year of the annual financial statements is December 31, and publishes complete annual financial reports so that a sample of 156 companies is obtained. Sample selection using purposive sampling method. The analysis used is multiple regression analysis. The results of this study indicate that solvency and good corporate governance affect the audit delay of financial statements. However, profitability and company size have no effect on audit delay financial statements. Keywords : Audit delay, ROA, DER, Size, GCG Index JEL Classification : M31,M41,M42